TRANSFORMASI PENDIDIKAN ISLAM MODERAT DALAM DINAMIKA KEUMATAN DAN KEBANGSAAN - S. Sofiuddin (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2018)
Abstract The paradigm of moderate Islamic education is increasingly attracting the attention of observers, researchers and experts from various quarters. But the ideas of each precisely the more different paradigms. In addition to the problems of moderate Islamic educational ideas that increasingly variant, it is more difficult to synergize to be a comprehensive concept, holistic, systematic, critical, integral and implementation. Discourses of thought about moderate Islamic education are still oriented to the prevention of drug problems, communism, the ideology of neo-liberalism, religious fundamentalism, radicalism-terrorism and so on. While the patterns of regular coaching through moderate Islamic education tend to get less attention. Through this paper, the authors will explain the mapping of the problem along with the possible opportunities for transforming moderate Islamic education in the community. Keyword: Moderate Education, Muslims, Nation